If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -8 + 2x = 2x + 4 Reorder the terms: -8 + 4x + 2x = 2x + 4 Combine like terms: 4x + 2x = 6x -8 + 6x = 2x + 4 Reorder the terms: -8 + 6x = 4 + 2x Solving -8 + 6x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 6x + -2x = 4 + 2x + -2x Combine like terms: 6x + -2x = 4x -8 + 4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 4x = 4 + 0 -8 + 4x = 4 Add '8' to each side of the equation. -8 + 8 + 4x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = 4 + 8 4x = 4 + 8 Combine like terms: 4 + 8 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| -3x+16=25-8x | | 25x-28=35x-142 | | 12x-3=9x+27 | | 10x-50x=0 | | (X-3)(c+3)=5x-13 | | 4x-20=8+6x | | 4x-30=8+6x | | -2(2x-3)+3(2x-1)=2(x-2x-2) | | 13v=5v^2-6 | | 9x^3+3x^2-50=0 | | X^2-8x+11=1 | | (-3xy)(6y)= | | (125b^6)^(-2/3) | | 3x/2-100=350 | | Cos(4x)-7Cos(2x)=8 | | (x-(-4-3i))(x-(-4-3i))(x+5)(x+5)=0 | | 3(11x+4)=21-(x+8) | | b+(-42)=-86 | | 0.3(11x+4)=2.1-(x+8) | | x=-5y+45 | | X=-2.3-(4.5-31/2) | | 1+9n= | | f=-2.3-(4.5-31/2) | | 2x^2+2y^2-7x+y=0 | | 4-5y-9y=32 | | 3/4y=15.26 | | -4y+x=19 | | -90-9y+y^2=0 | | x=-4y+2 | | -4c-10x= | | x^2+y^2-18x+6y-81=0 | | 2(5-2(-5))=20 |